Superoxide scavenging and Akt inhibition in myocardium ameliorate pressure overload-induced NF-κB activation and cardiac hypertrophy - Hingtgen, Shawn D. (American Physiological Society, 2010)
Recent studies from our laboratory and others have shown that increases in cytoplasmic superoxide (O(2)(·−)) levels and Akt activation play a key role in agonist-stimulated NF-κB activation and cardiomyocyte hypertrophy in vitro. In this study, we tested the hypothesis that adenovirus (Ad)-mediated intramyocardial gene transfer of cytoplasmic superoxide dismutase (AdCu/ZnSOD) or a dominant-negative form of Akt (AdDNAkt) in mice would attenuate pressure overload-induced increases in activation of the redox-sensitive transcription factor NF-κB and cardiac hypertrophy. Adult C57BL/6 mice were subjected to thoracic aortic banding (TAB) or sham surgery, and intramyocardial injections of viral vectors (AdCu/ZnSOD, AdDNAkt, or control) were performed. There was robust transgene expression in the heart, which peaked 6–7 days after injection and then declined to undetectable levels by 12–14 days. In mice injected with AdBgL II, TAB caused a significant increase in O(2)(·−) generation and cardiac mass at 1 wk, and these responses were markedly attenuated by AdCu/ZnSOD. In addition, TAB induced time-dependent activation of NF-κB in the myocardium as measured longitudinally by in vivo bioluminescent imaging of NF-κB-dependent luciferase expression. This was also abolished by intracardiac AdCu/ZnSOD or AdDNAkt, but not the control vector. The inhibition of Akt and O(2)(·−)-mediated NF-κB activation in TAB hearts was associated with an attenuation of cardiac hypertrophy. Since a direct cause-and-effect relationship between NF-κB activation and cardiomyocyte hypertrophy has been established previously, our data support the hypothesis that increased O(2)(·−) generation and Akt activation are key signaling intermediates in pressure overload-induced activation of NF-κB and cardiac hypertrophy.